Mediterranean diet and cognitive health: an update of available knowledge. Issue 1 (January 2015) - Feart, Catherine; Samieri, Cécilia; Barberger-Gateau, Pascale
Abstract : Purpose of review: Nutrition constitutes an interesting approach for the prevention of age-related brain disorders. The objective of this review was to examine the most recent evidence on the association between adherence to a Mediterranean diet (MeDi) and cognitive health among elderly individuals. Recent findings: Based on available epidemiological studies, two meta-analyses published in 2013 have underlined a protective effect of a greater MeDi adherence on cognitive health, including a reduced risk of Alzheimer's disease and cognitive impairment. Since then, six additional studies, from longitudinal cohorts or post-hoc analyses of randomized controlled trials conducted in the USA and Europe, have been published and provided mixed results. Potential reasons for such discrepancies include methodological limitations inherent to observational studies, and interactions between diet, environmental factors, such as those enhancing cognitive reserve, chronic diseases, and genetic factors. Summary: Overall, available evidence suggests that the MeDi might exert a long-term beneficial effect on brain functioning. However, more high-powered observational studies with long-term follow-up for cognition and randomized controlled trials assessing the impact of shifting to a MeDi on cognitive functions are still needed in various populations.